Manejo reprodutivo da piracanjuba (Brycon orbignyanus): congelamento de sêmen e taxas de fertilidade. - Felizardo, Viviane de Oliveira (2008)
This experiment has as an objective the application of biotechnology on the reproductive management of the piracanjuba seeking to improve the piracanjuba semen freezing techniques; to evaluate the best spermatoid dose to be used in ovocyte fertilization and to verify the influence of different water volumes used to activate the spermatoids in the fertilization. The work was accomplished at the CEMIG Fish Farming Station in Itutinga and in DMV-UFLA during the spwaning periods of 2006/2007/2008. The effect of 2 intracellular cryoprotector solutions was evaluated (DMSO and methanol) and 2 extracellular solutions (egg yolk and lactose), in the cryopreservation of the piracanjuba reproducer semen, having as evaluation parameters the rate and duration of the mobility and spermatic morphology; the the best semen volume to be used (10, 20, 30 and 40 µL) in the fertilization of ovocytes in the induced reproduction of piracanjuba and; the effect of the use of different volumes of water (5, 10, 20 and 40 mL) as a spermatoids ativating solution on the artificial fertilization rates of the ovocytes. All the experimental variables were analyzed using the Statistical Analysis System (SAS, 1999) program. No statistical difference (P>0.05) was observed among the used cryoprotectors tested. The semen/ovocyte relationship tested did not alter (P>0,05) the fertilization and hatching rates. The relationship of water volumes tested did not alter the fertility rate (P>0.05). In the piracanjuba semen cryopreservation protocol solutions containing DMSO or methanol can be as internal cryoprotectors and egg yolk or lactose as external cryoprotectors. In order to have a sustainable exploration in the induced reproduction of piracanjuba, the utilization of 10.4 x105 spermatoids/ovocytes and the activation with 5 mL of water from the reproductor tank is suggested.